Morphology Switching and Quorum Sensing in Candida Albicans Pathogenesis - Lim, Crystale Siew Ying (2010)
Candida albicans is the major etiological agent of invasive candidiasis. Although yeast-hyphae switching has been shown to be an important virulence factor, lately it has become evident that the phenomenon of quorum sensing, which also controls this switching, is a new and more important virulence factor. The first part of the present study was undertaken to identify novel C. albicans genes which may also be involved in yeast-hyphae switching. Autoradiogram data from differential display reverse transcription-polymerase chain reaction (DDRT-PCR) studies of the yeast and hyphal forms at selected time-points were recorded and analyzed. Using molecular methods and bioinformatics, 41 of these DDRT-PCR cDNA transcripts were identified as annotated genes involved in various biochemical, metabolic and physiological functions while 28 transcripts, with no significant homologies to any known C. albicans genes. Real-time PCR expression profiling of four out of nine selected DDRT-PCR trancripts agreed with the DDRT-PCR band intensity trends while six transcripts were found to be highly differentially expressed in biofilms. The discovery of more genes involved in the intricate pathways of C. albicans yeast-hyphae switching would contribute to the complete mapping of the morphology switching transcriptional network. The new transcripts, such as A2-5 (potential germ-tube biomarker), may also be further characterized and investigated as potential biomarkers of systemic candidiasis. The findings here as well as in recent studies suggest that C. albicans pathogenesis may be a consequence of environmental adaptation, as the genes described thus far to be involved in yeast-hyphae switching have been inseparable from genes involved in response to environmental signals. Hence, this study was also aimed at better understanding the phenomenon of quorum sensing (QS) as a major influence of yeast-hyphae switching. Here, 150 μM of a synthetic 12-carbon backbone molecule, 2-dodecanol, was demonstrated to prevent C. albicans hyphae development. Expression of SIR2, a gene involved in phenotypic switching, was shown in this study to be elevated during hyphae development, and this up-regulation was repressed with the presence of 2-dodecanol, thereby suggesting that SIR2 may be involved in quorum-sensing and/or hyphae development via the Ras-cAMP-EFG1 pathway. The final part of this study was aimed at investigating the in vitro host response to the three major morphological forms of C. albicans infections, as well as to farnesol, a QSM. Microarray transcriptome profiling of human umbilical vein endothelial cells (HUVEC) infection with C. albicans suggests that an initial high inoculum size of yeast cells evoked a stronger, broader range of transcriptional response than either pseudohyphae or hyphae at lower densities. In general, many of the genes which were mutually induced, such as CSF2, DDIT4 and FOS, are involved in apoptosis and cell death. In addition, the exclusive differential expression of certain HUVEC genes in response to a particular C. albicans morphology was observed, suggesting that each morphological form may have different roles in the host environment. HUVEC viability was also significantly reduced after treatment with conditioned media from high-density C. albicans-HUVEC co-cultures compared to media from low-density co-cultures. This led to the postulation that the C. albicans-HUVEC interaction resulted in the release of an unknown soluble factor(s) which, at a certain concentration, is capable of causing HUVEC cell death and therefore may be instrumental in pathogenesis. As discovered via transcriptome profiling of HUVEC treated with farnesol, during initiation of pathogenesis farnesol may interfere with the G-protein coupled receptor (GPCR) signal transduction of host cells. In addition, HUVEC treatment with farnesol concentrations of more than 100 μM in a high-alcohol-content solvent resulted in drastic cell death. Therefore, QS, critical in C. albicans response dynamism and adaptation to changes in a niche environment in the host, is likely a stronger virulence factor preceding yeast-hyphae switching in invasive candidiasis. In conclusion, through molecular genetics investigations, this study has elucidated several novel C. albicans transcripts of unknown functions and has revealed new aspects in the relationship between C. albicans QS, yeast-hyphae switching, and the host response, all of which contribute to a better fundamental understanding of C. albicans pathogenesis.